The correct answer is: " 4096 x⁶ " .
Step-by-step explanation:
Given: [(4x)³] ² ; Simplify.
Method 1)
Note the following multiplication property of exponents:
⇒ (aᵇ)ᶜ = a⁽ᵇ*ᶜ⁾ ;
As such:
[ [(4x)³] ² = (4x)⁽²ˣ³⁾ = (4x)⁶ ;
Now; note the following property of exponents:
(ab)ᶜ = aᶜ * bᶜ ;
As such: (4x)⁶ = 4⁶ * x⁶ ;
Now; we can simplify 4⁶ ; by using a calculator:
→ 4⁶ = 4096 ;
Or: 4⁶ = 4 * 4 * 4 * 4 * 4 * 4 ;
= (4 * 4) * 4 * 4 * 4 * 4 ;
= 16 * 4 * 4 * 4 * 4 * ) ;
= (16 * 4) * 4 * 4 * 4 ;
= 64 * 4 * 4 * 4 ;
= (64 * 4) * 4 * 4 ;
= (126 * 4) * 4
= (256) * 4 ;
= 4096 .
_______
or: 4⁶ = 4 * 4 * 4 * 4 * 4 * 4 ;
= (4 * 4) * (4 * 4) * (4 * 4) ;
= 16 * 16 * 16 ;
= (16 * 16) * 16 ;
= (256) * 16 , = 4096.
_______
So: [(4x)³] ² = 4⁶ * x⁶ = 4096 x⁶ ;
_______
Method 2) Given: [(4x)³] ² ;
(4x)³ = 4x * 4x * 4x ;
[(4x)³]² = (4x * 4x * 4x)²
= (4x * 4x * 4x) * (4x * 4x * 4x) ;
= (4 * 4 * 4 * x * x * x * 4 * 4 * 4 * x * x * x ;
= 4 * 4 * 4 * 4 * 4 * 4 * x * x * x * x * x * x ;
⇒ (4 * 4 * 4 * 4 * 4 * 4) = 4⁶ = 4096 ; (see Method 1 above).
⇒ (x * x * x * x * x * x) = x⁶ ;
⇒ [(4x)³] ² = 4⁶ * x⁶ = 4096 x⁶ ;
_______
Method 3)
[(4x)³] ² = (4x)⁽²ˣ³⁾ = (4x)⁶ ;
(4x)⁶ = 4x * 4x * 4x * 4x * 4x * 4x ;
= 4 * 4 * 4 * 4 * 4 * 4 * x * x * x * x * x * x ;
= (4 * 4 * 4 * 4 * 4 * 4) * (x * x * x * x * x * x) ;
⇒ (4 * 4 * 4 * 4 * 4 * 4) = 4⁶ = 4096 ; [see Method 1 above].
⇒ (x * x * x * x * x * x) = x⁶ ;
⇒ [(4x)³] ² = 4⁶ * x⁶ = 4096 x⁶ .
_______
The correct answer is: " 4096 x⁶ " .
_______
Hope this is helpful.
Best wishes in your academic endeavors!
_______